5+3r-3=8r+6-4r

Simple and best practice solution for 5+3r-3=8r+6-4r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+3r-3=8r+6-4r equation:


Simplifying
5 + 3r + -3 = 8r + 6 + -4r

Reorder the terms:
5 + -3 + 3r = 8r + 6 + -4r

Combine like terms: 5 + -3 = 2
2 + 3r = 8r + 6 + -4r

Reorder the terms:
2 + 3r = 6 + 8r + -4r

Combine like terms: 8r + -4r = 4r
2 + 3r = 6 + 4r

Solving
2 + 3r = 6 + 4r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-4r' to each side of the equation.
2 + 3r + -4r = 6 + 4r + -4r

Combine like terms: 3r + -4r = -1r
2 + -1r = 6 + 4r + -4r

Combine like terms: 4r + -4r = 0
2 + -1r = 6 + 0
2 + -1r = 6

Add '-2' to each side of the equation.
2 + -2 + -1r = 6 + -2

Combine like terms: 2 + -2 = 0
0 + -1r = 6 + -2
-1r = 6 + -2

Combine like terms: 6 + -2 = 4
-1r = 4

Divide each side by '-1'.
r = -4

Simplifying
r = -4

See similar equations:

| -2x+-4=4x-10 | | -1/2*4/1= | | x+12=3x+2 | | 99/3366 | | 2x+1+x=3(x-2)+7 | | 600=5x+10y | | (y-8)=2-4y | | 10x-5x-3=0 | | 5/6x-2/3=-4 | | x^4-12x^3+20x^2=0 | | 8x+2=3x+57 | | 3x+1=3(x-2)+7 | | 600= | | 7p^2+30p+8=0 | | 3n+11n=126 | | (3x-2)/8+(2-x)/4=-1/2 | | 2x^2+36=17x | | -2x+6-1.5x=1 | | -3x-2y=-7 | | x+y=2.5 | | x/16=-26 | | -9x+8y=8 | | 5x/8-2=15 | | 9=3(15-3x) | | 64-16t^2=0 | | 1.5f-2=1.6f | | 5(v-4)=2v-5 | | 12=3x-6y | | -16t^2+32=0 | | 9=3(15-3) | | 3x-6=0.5(4x+8) | | 8x+4y=-12 |

Equations solver categories